Secure Storage Implementation for Large Files in iOS Environment - Hovsepyan, Levon M.; Mayilyan, Aren K. (Mathematical Problems of Computer Science, 2021)
Mobile device storage services are not secure by nature as all databases and files are stored on the client side. We cannot ignore that because nowadays mobile devices are made of hardware, which is capable for building and running applications, which cover almost every functionality that computers have. There is an inherent risk of data exposure (confidentiality) and data tampering (integrity). To avoid the risks mentioned above, software engineers use some approaches, which are provided by the iOS SDK for securely storing sensitive data. However, those approaches currently work only for small amount of data (key-value pairs) and the issue still remains for large files. In this paper, we introduced an approach of securely storing large files in iOS environment.